Physical properties of Nano Crystalline Ceramic Ho1-xBaxCrO3. Issue 16 (November 2019) - Ben Youssef, R. Triki; Sdiri, Nasr; Valente, M.A.; Horchani-Naifer, K.; Férid, M.
Abstract: The set of Ho1-x Bax CrO3 with x = 0.0, 0.2, 0.3 was synthesized through sol – gel technique. Rietveld refinement of X-Ray Diffraction (XRD) patterns and Raman spectroscopy showed a single phase orthorhombic structure for all the samples. Raman analysis revealed the presence of the Ag phonon mode related to the existence of CrO6 octahedra. Thermal studies were performed to show a thermal stability of the compounds. Pl measurements exhibited not only visible light emission but also intense NIR emission under excitation of UV light. Impedance spectroscopy indicated that DC conductivity can be explained by Arrhenius-type thermally activated process for x = 0.0 and 0.2 whereas for x = 0.3, it obeyed to Mott's law. The conduction mechanism was found to be referred to polaron hopping. The dielectric measurements revealed a polarization in the as-prepared samples with high values of dielectric constant and low dielectric loss in particular for x = 0.3. Magnetic measurements showed enhancement of magnetisation upon Ba substitution and the existence of a large magnetocaloric effect.